Gender and Intimate Partner Violence in Latino Immigrant Neighborhoods - Soller, Brian (Journal of quantitative criminology, 2019)
Some quantitative studies indicate that overall rates of intimate partner violence (IPV) are lower in Latino immigrant neighborhoods, but numerous qualitative studies suggest residing in Latino immigrant enclaves increases women's risk of IPV victimization. We examine the association between neighborhood Latino immigrant concentration and (1) overall IPV and (2) tendencies towards female IPV victimization among resident couples.